Stakeholders’ attitudes towards biobanks in Malaysia - Hasrizul Hashim,; Latifah Amin,; Zurina Mahadi,; Khaidzir Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The Malaysian Cabinet’s approval of MyCohort in 2005 was seen as the crucial step toward the country having its very first biobank to improve the prevention, diagnosis and treatment of diseases. Past studies have shown that public attitudes towards biobanking depend heavily upon several factors including public engagement with biobanks, trust in key actors, privacy and data security, perceived benefit, altruism and certain demographic variables. The objective of this paper is to assess and compare the attitude levels of the Malaysian stakeholders’ towards the application of biobanks across education levels and religion. A survey was carried out on 509 adult respondents in the Klang Valley region of Malaysia. Results of the study have substantiated that the Malaysian stakeholders’ attitudes towards biobank were classified as high. Despite their high levels of perceived benefit and religious acceptance, they also expressed moderately high levels of concern when it comes to issues of data and specimen protection; this suggests that the Malaysian stakeholders also tend to be critical upon expressing their views towards a complex system such as biobanks. One-way MANOVA initially has detected a significant difference of attitude towards biobanks across stakeholder groups, education level and religion. Series of univariate analysis following the MANOVA, as well as Post Hoc analysis, also confirm significant difference of attitude existing across stakeholders; however, no significant differences were detected across education level and religion. The research finding serves as a useful benchmark for scientists and government regulators to understand public attitudes to biobanks before they are set into use.